Automotive electronic control unit (ECU) / Muhammad Haris Md Salleh, Abdul Aziz Ibrahim and Aminuddin Illias - Md Salleh, Muhammad Haris; Ibrahim, Abdul Aziz; Illias, Aminuddin (2002)
Nowadays, fully integrated electronic control systems are state-of-the-art, standard equipment on most cars. Current systems use an Electronic Control Unit(ECU). The ECU is electronic devices able to draw the conditions of exercise of the engine and to modify the functioning of the interested organs; they govern all the vital function of the engine, from the fuel injector in the cylinder to the correct phase of spark in the combustion chamber and the other. The reason was the ECU has brought more engine functions under electronic control with best performance, fuel economy and emission control. It's absolutely needed by automotive vehicles. The basic parts of an ECU are the inputs, the control unit (decision-maker), and the outputs. The inputs devices are sensors, the output are the actuators. The decision maker or control unit is microprocessor.